KELEKATAN DAN CRITICAL THINGKING DENGAN INTENSITAS MENGAKSES PORNOGRAFI PADA DEWASA YANG SUDAH MENIKAH - Hasini, Nifa Ulida; Pramintari, Ratna Duhita; Nurhidayah, Siti (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2025)
Married adults have greater responsibilities than unmarried adults. They should be responsible for themselves, their partners, and their children, if any. This research is a quantitative research using a population of 240 respondents as a sample, the sample technique used is quota sampling, which is a technique to determine samples from populations that have certain characteristics to the desired number of Sugiyono (2016). And the Critical Thinking Questionnaire scale instrument created by Alexander, et al (2022) with a validity value of 0.94 and a reliability Alpha Cronbach value of 0.871. In the instrument, the adhesion uses a self- arranged scale by racing on Collin's theory (1996) with a validity value with a value range from 0,81 – 1,00 and an Alpha Cronbach reliability value of 0,821. Furthermore, the intensity of accessing pornography is arranged by itself in a race on Ajzen's theory (1991) with a validity value with a value range from 0.94 and an Alpha Cronbach reliability value of 0,837.The results of the research on the spearman rank test have a relationship between attachment and intensity of accessing pornography with a value of r = -259, p =0,000 (p< 0.05), then critical thinking with intensity of accessing pornography with a value of r = - 386, p = 0,000 (p< 0.05). This shows that the higher the attachment, the lower the intensity of accessing pornography and the higher the critical thinking, the lower the intensity of accessing pornography